2017
DOI: 10.1080/14786419.2017.1283495
|View full text |Cite
|
Sign up to set email alerts
|

A new compound, methylbergenin along with eight known compounds with cytotoxicity and anti-inflammatory activity from Ardisia japonica

Abstract: A new compound, methylbergenin (1), was isolated from the whole plants of Ardisia japonica (Thunb.) Bl. (Myrsinaceae), along with eight known compounds: demethoxybergenin (2), bergenin (3), afzelin (4), quercitrin (5), bauerenol (6), bauerenone (7), α-spinasterol (8) and chondrillasterone (9). Compounds 1, 7 and 9 were isolated from A. japonica for the first time. The structure of compound 1 was determined on the basis of NMR (1D and 2D) and mass spectroscopic analysis. The absolute configuration of 1 was asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…Kaempferol and afzelin are natural flavonoids found in different plant species. Kaempferol is a major flavonoid aglycone found in many plants and displays several promising biological activities, such as antimicrobial, antioxidant, antitumor, cardioprotective, neuroprotective, and antidiabetic, as well as anti-inflammatory. , Studies have also demonstrated the potential of afzelin as an anti-inflammatory, antioxidant, , skin protector, , and hepatic and renal protector agent. , Based on the introduction above and considering that B. forficata preparations and kaempferitrin have already demonstrated diuretic potential in previous studies, and knowing that afzelin and kaempferol are both active compounds from its metabolism, this study aimed to evaluate, for the first time, the acute and prolonged diuretic properties of these compounds, in addition to demonstrating afzelin’s mode of action in promoting diuresis and renal protection.…”
mentioning
confidence: 99%
“…Kaempferol and afzelin are natural flavonoids found in different plant species. Kaempferol is a major flavonoid aglycone found in many plants and displays several promising biological activities, such as antimicrobial, antioxidant, antitumor, cardioprotective, neuroprotective, and antidiabetic, as well as anti-inflammatory. , Studies have also demonstrated the potential of afzelin as an anti-inflammatory, antioxidant, , skin protector, , and hepatic and renal protector agent. , Based on the introduction above and considering that B. forficata preparations and kaempferitrin have already demonstrated diuretic potential in previous studies, and knowing that afzelin and kaempferol are both active compounds from its metabolism, this study aimed to evaluate, for the first time, the acute and prolonged diuretic properties of these compounds, in addition to demonstrating afzelin’s mode of action in promoting diuresis and renal protection.…”
mentioning
confidence: 99%
“…Standardization of planting, harvesting, and processing is strongly recommended to assure the quality consistency of AJH. Since bergenin and quercitrin have been reported to show potent biological activities , considering their contents in AJH samples, these two compounds are proposed as suitable chemical markers for QC of AJH.…”
Section: Resultsmentioning
confidence: 99%
“…Our recent study has described the isolation and structural characterization of a new coumarin compound, methylbergenin, along with eight known compounds from AJH. The isolated compounds displayed cytotoxicity and anti‐inflammatory activity . Characterization of the chemical constituents in AJH is helpful for the identification of potential compounds responsible for the biological functions and provides hints for further development of new drug.…”
Section: Introductionmentioning
confidence: 99%
“…Pyranopyrans in which the two rings are cis-fused are relatively rare compared to trans-fused pyranopyrans (Giuliano, 2014). A consequence of the cis ring fusion is that the molecule has more of a bent shape than it would if trans-fused, which is demonstrated by the O1-C8A-C4A-O5 torsion angle of 72.95 (15) versus 177 for a comparable trans-fused pyranopyran (Yu et al, 2017). Both rings adopt half-chair conformations, placing the amide group in a near 1,3-diaxial interaction with H4A.…”
Section: Structural Commentarymentioning
confidence: 99%